Climate Change, Laudato Si', Creation Spirituality, and the Nobility of the Scientist's Vocation - Fox, Matthew (Zygon, 2018)
This exploration into spirituality and climate change employs the four paths of the creation spirituality tradition. The author recognizes those paths in the rich teachings of Pope Francis's encyclical, Laudato Si' and applies them in considering the nobility of the scientist's vocation. Premodern thinkers often resisted any split between science and religion. The author then lays out the basic archetypes for recognizing the sacredness of creation, namely, the Cosmic Christ (Christianity); the Buddha Nature (Buddhism); the Image of God (Judaism); the Primordial Man (Hinduism), as well as the premodern universal teaching of God as Beauty. He addresses the subject of evil which deserves serious attention in the face of the realities posed by climate change and the resistance to addressing them. In the concluding section, the author speaks of a new Order of the Sacred Earth that was launched in fall 2017 to gather persons of whatever spiritual tradition or none to devote themselves to preserving Mother Earth.